1989
DOI: 10.1111/j.1432-1033.1989.tb15222.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of P2Y purinoceptors associated with voltage‐activated cation channels in cardiac ventricular myocytes of the rat

Abstract: Extracellular ATP has vasodilatory and inotropic effects in the heart. We have demonstrated that extracellular ATP, in a concentration-dependent manner (1 0 nM -0.1 mM), increased [Ca' 'Ii in suspensions of isolated fura-2-loaded rat cardiac ventricular myocytes (maximum 96 f 10% increase over basal levels, SEM, n = 12, P < 0.01).The increase in [Ca2+Ii was often biphasic, with an initial fast phase ( < 1 s) of low amplitude, followed by a slower phase of higher amplitude. A second application of ATP had litt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
28
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 52 publications
5
28
0
Order By: Relevance
“…The Ca2+ rise as previously reported by others [7,24,26,27] and during the present work has at least three origins. (1) [7][8][9] to the deleterious ventricular arrhythmias expected from the above results.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The Ca2+ rise as previously reported by others [7,24,26,27] and during the present work has at least three origins. (1) [7][8][9] to the deleterious ventricular arrhythmias expected from the above results.…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, Sharma & Sheu [24] and De Young & Scarpa [25,26] showed that ATP triggered a large Ca2+ transient, followed by a weaker sustained increase, whereas others [7] found only a slow rise in intracellular Ca2". More recently, ATP was demonstrated to trigger a membrane depolarization associated with the rapid Ca2+ transient [27]. These effects of ATP on…”
Section: Introductionmentioning
confidence: 96%
“…The subtype classification of P2-purinoceptor therefore remains to be determined although our data might also indicate the presence of P2y-purinoceptors in rat ventricular myocytes (Bjornsson et al, 1989).…”
Section: Response To Various Purinoceptor Agonistsmentioning
confidence: 99%
“…This decrease in ICa has been attributed to occupancy of P2y-purinoceptors, with 2-methylthio-ATP being more potent than a,-methylene-ATP (Qu et al, 1993b). The transient increase in Ca, (in rat) and the positive inotropism ( in rat and guinea pig) induced by ATP have also been attributed to P2y purinoceptors (Bjornsson et al, 1989;Mantelli et al, 1993;Wang et al, 1993). In the present study we have investigated the pharmacological profile of ATP-activated non-specific cationic current and the increase in Ica in rat ventricular myocytes, which are supposed to be largely responsible for the changes in Ca, and the positive inotropism.…”
mentioning
confidence: 99%
“…In rat cardiac preparations, ATP is reported to have positive inotropic effects and to increase the Ca2+ transients of electrically stimulated cells (Danziger et al, 1988;Legssyer et al, 1988). It has also been reported that ATP transiently increases the intracellular Ca2' concentration, Ca,, of quiescent cells (De Young & Scarpa, 1987;Danziger et al, 1988;Bjornsson et al, 1989;Puceat et al, 1991a;Hirano et al, 1991). In addition, electrophysiological studies have shown that ATP activates a nonspecific cationic current in frog, rat and guinea pig cardiac cells (Friel & Bean, 1988;; Matsuura & Ehara, 1992), an inwardly rectifying K+ channel in frog (Friel & Bean, 1990) and a chloride current in guinea pig (Matsuura & Ehara, 1992), increases the L-type calcium current amplitude in rat Zheng et al, 1993) and increases both the L-and T-type in frog cells (Alvarez & Vassort, 1992).…”
mentioning
confidence: 99%